THE ROLE OF PARENTAL SUPPORT ON LEARNING ACHIEVEMENT OF JUNIOR HIGH SCHOOL STUDENTS IN YOGYAKARTA - Wasito, Wasito; Ismail, Nawari; Adi Kistoro, Hanif Cahyo (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
One of the important parts of a person's life is an achievement. because the desire to achieve is part of the social motives that a person has. Among the social motives is the motive to achieve because it will be able to improve performance and try to achieve maximum achievement. Achievement in the world of education is a consequence of various interests that connect various factors including family, community, school, peers and the students themselves. This study aims to determine the contribution of parental support to junior high school student achievement. This research design is to reveal various things that are summarized in a construct or dynamics of parental support on achievement. The research subjects were 248 junior high school students in Yogyakarta. Data collection in this study used a qualitative survey method with open-ended question type interviews. The results showed that the contribution of direct social support from the family played the most role in achievement, which amounted to 84.4 percent in the subject, followed by friends by 7.0 percent and teachers by 5.8%. From these results it is clear that the contribution of direct social support from family followed by friends and teachers is the most instrumental contribution to student achievement.